Removal of Methylene Blue from an Aqueous Solution using Prepared Activated Carbon from Olive Woods - Hussien, Nour Alaa Aldein (American Journal of Biomedicine and Pharmacy, 2025)
The present study was aimed to remove Methylene Blue dye by adsorption technique using activated carbon as an adsorbent and study some factors, including contact time, adsorbent content, and beginning dye concentration, influence the adsorption process. Production of Activated Carbon (A.C) from Iraqi woods (olive) by cutting the woods to small sizes and the produce charcoal by using heating process and the convert the charcoal into carbon by heating the woods in the furnace with the absence of oxygen at higher temperature (500 c0) the next steps the Activations of carbon prepare the (KOH) solution (3/1) by weight and left the Carbon in the (KOH) solutions (24 hours) after 24 hours put the activated carbon in the Electrical furnace with higher temperature to (1hour) to increase the surface area for adsorptions. after the production of activated carbon and prepared methylene blue solutions with different concentrations (20,40,60, 80) ppm put the activated carbon with known weights in the methylene blue solution and mixed them some minutes noticed that the concentrations ppm of methylene blue reduced.